AQA a-Level Business Student Guide 2 - Pickerden, Mike (Hodder Education Group, 2020)
Reinforce your understanding of managers, leadership and decision-making with this AQA A-level Business Student Guide. This book covers Themes 1-7 of the 10 themes in A-level Business, which can be examined in all three A-level papers: -Analysing the strategic position of a business -Choosing strategic direction -Strategic methods: how to pursue strategies -Managing strategic change This Student Guide will help you to: -Identify key content for the exams with our concise coverage of topics -Avoid common pitfalls with clear definitions and exam tips throughout -Reinforce your learning with bullet-list summaries at the end of each section -Test your knowledge with rapid-fire knowledge check questions and answers -Find out what examiners are looking for with our Questions & Answers section